Pengaruh Rekrutmen dan Kompetensi Terhadap Kualitas Karyawan Serta Impilikasinya Terhadap Kinerja Karyawan Pada PT. Jaya Palopo Tehnik - Karno Karno; Trimei Ernita (Fakultas Ekonomi Universitas Borobudur, 2020)
This study aims to determine the extent of the influence of recruitment and competence onemployee quality and its implications for employee performanceThe data used in this study are primary data collected from respondents' answers based onthe questionnaire given, as many as 80 people. The data processing method uses the path analysismethod with the help of SPSS version 22.0. Statistical testing used individual parametersignificance test (t test), simultaneous significance test (F test) and Sobel test.The results showed that recruitment had a positive and significant effect directly onemployee quality, competence had a positive and significant effect directly on employee quality,recruitment had a positive and significant effect directly on employee performance, competencyhad a positive and significant effect directly on employee performance, employee quality. receiveda positive and significant effect directly on employee performance.Keywords: recruitment, competence, employee quality and employee performance